2012
DOI: 10.1089/thy.2012.0045
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiles in Familial and Sporadic Medullary Thyroid Carcinoma: Preliminary Relationships with RET Status and Outcome

Abstract: Background: MicroRNAs (miRNAs) are involved in the pathogenesis of human cancers, including medullary thyroid carcinoma (MTC). The aim of this study was to test the hypothesis that different miRNA profiles are related to RET status and prognosis in patients with hereditary MTC (hMTC) and sporadic MTC (sMTC). Methods: We analyzed the expression of nine miRNAs (miR-21, miR-127, miR-154, miR-224, miR-323, miR-370, miR-9*, miR-183, and miR-375) by quantitative real-time-polymerase chain reaction in 34 cases of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 24 publications
5
86
0
1
Order By: Relevance
“…Overall, RAS mutations were present in 69.2% (18/26) of the RET WT cases and in only 2.5% of the RET-positive sporadic MTC (P!0.0001), suggesting that activation of the protooncogenes RAS and RET represents alternative genetic events in sporadic MTC tumorigenesis. These results were confirmed by other groups , Schulten et al 2011, Boichard et al 2012, Mian et al 2012, Tamburrino et al 2012, Ciampi et al 2013, Nikiforova et al 2013, Lyra et al 2014, Simbolo et al 2014, Pennelli et al 2015. We found no other mutations in the entire coding region of the genes HRAS, KRAS and RET in the RET and RAS WT sporadic MTC (M M Moura, B M Cavaco and V Leite, unpublished observations).…”
Section: Ras Mutations In Mtcsupporting
confidence: 91%
See 4 more Smart Citations
“…Overall, RAS mutations were present in 69.2% (18/26) of the RET WT cases and in only 2.5% of the RET-positive sporadic MTC (P!0.0001), suggesting that activation of the protooncogenes RAS and RET represents alternative genetic events in sporadic MTC tumorigenesis. These results were confirmed by other groups , Schulten et al 2011, Boichard et al 2012, Mian et al 2012, Tamburrino et al 2012, Ciampi et al 2013, Nikiforova et al 2013, Lyra et al 2014, Simbolo et al 2014, Pennelli et al 2015. We found no other mutations in the entire coding region of the genes HRAS, KRAS and RET in the RET and RAS WT sporadic MTC (M M Moura, B M Cavaco and V Leite, unpublished observations).…”
Section: Ras Mutations In Mtcsupporting
confidence: 91%
“…In a large series of 64 MTC (56 sporadic and eight familial), Pennelli et al (2015) demonstrated significant PDCD4 nuclear downregulation together with miR-21 upregulation, thus confirming their previous results obtained in a small series of MTC (Mian et al 2012), and showed also that miR-21/PDCD4 expression correlates with clinicopathological findings and prognosis. Although these authors were unable to detect any significant correlation between the miR-21/PDCD4 pathway and somatic RET or RAS mutation status, they found that the six RAS-positive cases in their series of MTC sporadic tumors had higher nuclear PDCD4 expression levels than the RET-positive/RAS-negative or RET/RAS WT patients.…”
Section: Micrornasupporting
confidence: 86%
See 3 more Smart Citations